Exercise during short‐term exposure to hypoxia or hyperoxia ‐ novel treatment strategies for type 2 diabetic patients?!. (26th July 2017) - Brinkmann, C.; Bloch, W.; Brixius, K.
Abstract : Both hypoxia (decreased oxygen availability) and hyperoxia (increased oxygen availability) have been shown to alter exercise adaptations in healthy subjects. This review aims to clarify the possible benefits of exercise during short‐term exposure to hypoxia or hyperoxia for patients with type 2 diabetes mellitus (T2DM). There is evidence that exercise during short‐term exposure to hypoxia can acutely increase skeletal muscle glucose uptake more than exercise in normoxia, and that post‐exercise insulin sensitivity in T2DM patients is more increased when exercise is performed under hypoxic conditions. Furthermore, interventional studies show that glycemic control can be improved through regular physical exercise in short‐term hypoxia at a lower workload than in normoxia, and that exercise training in short‐term hypoxia can contribute to increased weight loss in overweight/obese (insulin‐resistant) subjects. While numerous studies involving healthy subjects report that regular exercise in hypoxia can increase vascular health (skeletal muscle capillarization and vascular dilator function) to a higher extent than exercise training in normoxia, there is no convincing evidence yet that hypoxia has such additive effects in T2DM patients in the long term. Some studies indicate that the use of hyperoxia during exercise can decrease lactate concentrations and subjective ratings of perceived exertion. Thus, there are interesting starting points for future studies to further evaluate possible beneficial effects of exercise in short‐term hypoxia or hyperoxia at different oxygen concentrations and exposure durations. In general, exposure to hypoxia/hyperoxia should be considered with caution. Possible health risks—especially for T2DM patients—are also analyzed in this review.